Legal Comparison of Counter-Terrorism Regulations in Indonesia and Malaysia - Yasman, Viora Andari; Aminanto, Muhamad Erza; Lutan, Ahwil (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to explain the legal comparison of counterterrorism regulations in Indonesia and Malaysia. This is qualitative descriptive research which uses descriptive analysis. This research employs case approach and statute approach. The data was collected from primary legal materials as well as secondary legal materials. The findings reveal that anti-terrorism countermeasures have been governed in Indonesia by the anti-terrorism act, which focuses on countermeasures after a terrorist attack and prevention which gives Densus 88 the authority to investigate individuals suspected of being part of a terrorist group. Meanwhile, Malaysia has issued the ISA or Internal Security Act since 1960 as a form of defense against terrorist groups. The ISA is a regulation dealing specifically with terrorism cases, in which there are amendments in the form of authority granted to national security forces to arrest and detain individuals who are considered dangerous to national security without justice for 2 years. This policy ultimately created friction among the people because it was considered a weapon that could silence people's aspirations. With the many polemics and cons that side by side with the ISA, this is what ultimately made Malaysia revoke the ISA. As such, it can be concluded that terrorism cases are not cases that can be ignored because they involve life safety and national stability. The legal foundations for this issue must take into account a number of factors, including the principle of humanity or human rights. Regulations made specifically to handle this case will be one of the important points in the sovereignty and stability of a country, this is because terrorism cases involve many aspects in that country.